Measuring the key components of the user experience in immersive virtual reality environments - Cheiran, Jean Felipe Patikowski; Bandeira, Denise Ruschel; Pimenta, Marcelo Soares (Frontiers in Virtual Reality, 2025)
Researchers and practitioners frequently employ questionnaires to evaluate the User Experience (UX) mainly due to their cost-effectiveness, systematic nature, and ease of application. However, the use of questionnaires may be constrained by the availability of standardized instruments and the psychometric quality of the questionnaires. This paper presents the index of User Experience in immersive Virtual Reality (iUXVR), a questionnaire designed to measure key aspects of User Experience in immersive Virtual Reality (VR) environments based on the Components of User Experience framework. The questionnaire comprises seven-point Likert-like statements divided into five components: usability, sense of presence, aesthetics, VR sickness, and emotions. The development of the iUXVR was based on a content analysis of existing questionnaires, followed by an expert review and a pilot study. The iUXVR was applied in an experiment that collected 126 thoroughly answered questionnaires. The PLS-SEM analysis identified items with low factor loadings and low explained variance that have been removed from the questionnaire. The questionnaire presented good indicator loadings and adequate reliability estimates even though the items from aesthetics and emotions components are substantially correlated. The structural model suggests that VR sickness does not play an important role in the overall UX, even though it affects users’ emotions. On the other hand, the aesthetic experience, which is often neglected in UX models for VR environments, is essential in this context due to its strong relationship with emotions and UX. Furthermore, the sense of presence has less influence on the UX than usability, aesthetics, and emotions. Finally, the validity-supporting evidence is sufficient for exploratory research, substantiating consistent key aspects of the User Experience in immersive VR.